THEME: EDUCATIONAL WORK METHODS WITH YOUNG ARMWRESTLING SPORTSMEN IN TRAINING GROUPS (Proceedings of International Educators Conference, 2023)
This article covers the educational work methods with young armwrestling sportsmen in training groups. In order to solve this problem, in-depth analysis of competitive activity, motor skills, tactical thinking was conducted, as well as the factor structure of competitive activity indicators. The results obtained in the present study, can be used in planning and conducting the training process by trainers of junior teams, as well as performance of sportsmen in competitions.